Medical students' risk perceptions on decreased attention, physical and social risks in using mobile phones and the factors related with their risk perceptions. Issue 3 (4th May 2019) - Simsek, Hatice; Hassoy, Hur; Oztoprak, Dilek; Yilmaz, Tuba
ABSTRACT: The aim of this cross-sectional study is to determine the mobile phone use, risk perception and related factors among the medical students. The study population was 1465 medical students. The dependent variable was the risk perception on mobile phones. The risk perception was assessed in three dimensions: decreased attention, physical risks and social risks. The exploratory factor analysis was used for the success of the scale, and the factor loadings were calculated using the varimax rotation method. Logistic Regression Analysis was applied to determine the factors associated with risk perception. The presented results are based on 1079 students (Access rate = 73.7%). In all dimensions of risk perception, more than half of the medical students had high risk perceptions. Female students and lower social classes had high risk perceptions. An understanding of the determinants and mobile phone utilization characteristics might help in developing effective risk communication to these subgroups.